A Case Study on the Gas Drainage Optimization Based on the Effective Borehole Spacing in Sima Coal Mine. (8th September 2021) - Ji, Ming; Sun, Zhong-guang; Sun, Wei
Abstract : Based on the dynamic expressions of permeability and porosity of the coal seam derived in the paper, a multiphysical field coupling numerical model of gas migration under the interaction of stress field and seepage field was established. The gas drainage project #3 Coal Seam operated by Sima Coal Industry Co., Ltd., was selected as the study object. Taking different drainage time periods in various positions of drainage holes into consideration, combined with the advance situation of the 1207 working face in the Sima Coal Mine, a mixed layout gas drainage scheme featured with the effective borehole spacing was obtained through the COMSOL multiphysics simulation. In addition, a series of field industrial tests were performed to validate the research result, revealing that comprehensively considering the extraction time of coal and optimizing the layout of extraction boreholes can effectively improve the engineering economic benefits.